2015
DOI: 10.1108/amhid-02-2015-0011
|View full text |Cite
|
Sign up to set email alerts
|

“Why can’t they be in the community?” A policy and practice analysis of transforming care for offenders with intellectual disability

Abstract: Advances in Mental Health and Intellectual DisabilitiesPurpose: This paper describes key policy and practice issues regarding a significant subgroup of people with intellectual disability -those with offending behaviour being treated in forensic hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 17 publications
(19 reference statements)
0
40
0
Order By: Relevance
“…Alexander et al 106 ), and most studies have found that severe mental illness was associated with longer and PD with shorter LoS (e.g. Shah et al 42 ).…”
Section: Factors Associated With Length Of Staymentioning
confidence: 99%
“…Alexander et al 106 ), and most studies have found that severe mental illness was associated with longer and PD with shorter LoS (e.g. Shah et al 42 ).…”
Section: Factors Associated With Length Of Staymentioning
confidence: 99%
“…A number of authors have suggested that a lack of secure services for LD patients might contribute to their higher LoS [28] and most studies have found that severe mental illness was associated with longer and PD with shorter LoS [11]. This study did not use formal diagnostic data, but diagnostic ward type was used as a proxy and reflects these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The needs of people autism with or without intellectual disabilities with behaviour that challenges (who should be wholly supported in their own home) are different to the needs of those with additional mental illness; who may also require hospital treatment in the same way that the general population would according to the severity of their illness (Alexander et al, 2015). This distinction is important as people with behaviour that challenges or Autism alone should not be in hospital and it is absolutely right that we have policies that aim to end this practice, however people with intellectual disabilities or Autism with mental illness will on occasion require a specialist hospital admission in an ATU due to the relapsing and remitting nature of mental illness and the complications associated with an intellectual disability (RCP Faculty of Psychiatry of Intellectual Disability, 2013, pp.…”
Section: Discussionmentioning
confidence: 99%